Online Gambling Disorder Questionnaire (OGD-Q): An item r'esponse theory examination. (December 2022) - Stavropoulos, V.; Monger, K.; Zarate, Daniel; Prokofieva, Maria; Schivinski, Bruno
Highlights: Gambling disorder behaviours differ in their diagnostic weight/importance. OGD-Q reliably differentiates between individuals at different trait levels. Salience is indicated as the most representative symptom of problematic gambling. Abstract: Gambling disorder behaviours, such as one's preoccupation with gambling and/or mood modification due to gambling, have been proposed to differ in their diagnostic weight/importance, especially when informing diagnostic scales. Such potential differences are imperative to be considered to improve assessment accuracy. The latter is particularly important in the light of the rapidly increasing gambling opportunities offered online. To contribute to this area of knowledge, the current study assessed an online adult community sample ( N = 968, Mage = 29.5 years, SDage = 9.36 years) regarding their responses on the Online Gambling Disorder Questionnaire (OGD-Q). Item response theory (IRT) procedures examined the psychometric properties of the instrument, at both the item and the scale level. Results indicated that the OGD-Q demonstrated good capacity to reliably assess problem gambling and differentiate between individuals at similar levels of the trait, particularly between 1 and 3 SDs above the mean. The findings also showed OGD-Q components/items possess varying discrimination capacities, whilst they also differ in reliability across respondents with different levels of disordered gambling behaviours. Thus, it is supported that consideration is required regarding the differential weighting of one's item responses in the assessment procedure, taking concurrently into account their severity of disordered gambling behaviours.